Flow Boiling Heat Transfer Enhancement by Using ZnO-Water Nanofluids - Om Shankar Prajapati; Nirupam Rohatgi (Science and Technology of Nuclear Installations)
Nanofluids are liquid suspensions containing nanoparticles that are smaller than 100 nm. There is an increased interest in nanofluids as thermal conductivity of nanofluids is significantly higher than that of the base liquids. ZnO-water nanofluids with volume concentration of ZnO particles varying from 0.0001 to 0.1% were prepared using ultrasonic vibration mixer. Thermal conductivity of the ZnO-water fluids was investigated for different sonication time using thermal property analyzer (KD2 Pro). Thermal conductivity of nanofluids for a given concentration of nanoparticle varies with sonication time. Heat transfer coefficient and pressure drop in an annular test section with variable pressure (1–2.5 bar) and heat flux (0–400 kW/m2) at constant mass flux of 400 kg/m2s were studied for samples having maximum thermal conductivity. Surface roughness of the heating rod was also measured before and after the experimentation. The study shows that heat transfer coefficient increases beyond the base fluid with pressure and concentration of ZnO.